An analysis of teachers’ perceptions towards teamwork - Salleh, Mohamad Johdi; Kayode, Bakare Kazeem (ASIAN JOURNAL OF MANAGEMENT RESEARCH, 2014)
The study aims to examine the teachers’ perceptions and the underlying dimensions of their responses towards the concept of teamwork. The study involved 202 teachers of primary and secondary schools in the district of Kuantan, Malaysia. They were different age, gender, level of education, level of teaching, numbers of teaching years and marital status. The revised Teamwork Skills Questionnaire (TSQ) by O’Neil, Lee, Wang and Mulkey (1999) were adapted by the researchers as the primary instrument of data collection. The study applied the reliability and principal component analysis, with varimax rotation in order to produce the simplest factor structure. The inter-item relationships were examined to establish the reasonableness of the dimensional analysis. This study also applied Kaiser’s (1960) and Guadagnoli and Velicer’s (1988) criterion for important factors, significance test on factor loadings (Cliff and Hamburger, 1967), and, the interpretability of the extracted factors were used to decide on the number of factors to be retained. The final five-factor structure obtained from this investigation suggests that the TSQ is a multidimensional scale looking into various dimensions of perceptions towards teamwork. This paper further discuss on these dimensions in terms of the degree to which they reflect the emerged themes of perceiving teamwork. The use of principal component analysis in analyzing the responses gathered from the TSQ has helped to identify the emerging of two new themes in addition to the three initial themes. The findings are beneficial to understand and determine the success or failure of the practice of teamwork in the educational institutions especially the school. It will further aid teachers, educators, administrators, and professional development coordinators to adequately prepare, train, and support teachers so that they may become effective members of the team.